Application of Time Series Decomposition Techniques of Admission Patterns in Orphanage Homes - Emmanuel Fidel Ononuju; Audu Isah; Joshua ThankGod (Darul Yasin Al Sys, 2025)
This study applies decomposition technique on the admission of orphans and vulnerable children (OVC) into orphanage homes. Present studies have dwelt more on the number of OVC, the estimation of the parents that are dead, and the socioeconomic well-being of OVC. Hence, there is need to study the pattern of OVC admittance. Monthly data were collected from Niger state orphanage home register and documented for a period of twenty years (2000-2020). A time series decomposition analysis was carried out to determine an appropriate model, investigate the trend of admission of OVC, and establish if there is a seasonal pattern in the series. Results showed that the pseudo-additive model was most appropriate for the series which showed a decreasing linear trend. The study also showed that there is a seasonal pattern that has the second and third quarters of the year with the highest incidence of admission into orphanage home.